PERAN MEDIA SOSIAL PADA PROSES AGENDA SETTING DALAM FENOMENA VIRAL-BASED POLICY (STUDI KASUS: REVISI UU PILKADA DI KOTA SEMARANG) - Nuzulul Magfiroh; Hardi Warsono (Journal of Management and Public Policy, 2026)
This research is motivated by the phenomenon of viral-based policy, a condition in which public policy is influenced by issues that become viral on social media. The case of the Revision of the Pilkada Law in August 2024 demonstrates the significant role of social media as a public discourse arena that can influence the national policy agenda down to the local level, including in Semarang City. This research aims to analyze the role of social media in the policy agenda setting process through the perspectives of policy actors and the public in Semarang City. This research employs a descriptive qualitative method using the Multiple Streams Framework (MSF) proposed by John W. Kingdon. Data were collected through indepth interviews with informants from the Semarang City Regional House of Representatives, the Semarang City General Election Commission, local media journalists, and student activists. The data were further strengthened through digital observation and digital data extraction (data crawling) from the X platform. The findings indicate that within the problem stream, public conversations on social media increased the visibility of the Pilkada Law revision issue and shaped public attention toward the issue. However, some institutional actors at the local level perceived that the issue was not directly considered an urgent problem for the local community. Within the policy stream, two policy alternatives emerged in public discourse on social media: continuing the proposed revision by the House of Representatives or canceling the revision while adhering to the Constitutional Court’s decision. In the political stream, increasing public attention in digital spaces encouraged political responses from local actors, such as conveying public aspirations to the central government. These dynamics contributed to increasing political attention toward the Pilkada Law revision issue, which eventually led to the cancellation of the ratification of the revision at the national level. This study concludes that social media functions as a key catalyst in opening a policy window by bringing together the three streams, thereby enabling reactive shifts in the government’s agenda. Therefore, this study recommends that the government strengthen its social media listening capacity as a proactive instrument for capturing public aspirations, while balancing digital responsiveness with thorough technocratic policy analysis to maintain the quality of public policymaking.